Providing cell phone numbers and e-mail addresses to patients: The patient's perspective, a cross sectional study - Peleg Roni; Nazarenko Elena (BMC, 2012)
Abstract Background Today patients can consult with their treating physician by cell phone or e-mail. These means of communication enhance the quality of medical care and increase patient satisfaction, but they can also impinge on physicians' free time and their patient schedule while at work. The objective of this study is to assess the attitudes and practice of patients on obtaining the cell phone number or e-mail address of their physician for the purpose of medical consultation. Methods Personal interviews with patients, 18 years of age or above, selected by random sampling from the roster of adults insured by Clalit Health Services, Southern Division. The total response rate was 41%. The questionnaire included questions on the attitude and practice of patients towards obtaining their physician's cell phone number or e-mail address. Comparisons were performed using Chi-square tests to analyze statistically significant differences of categorical variables. Two-tailed p values less than 0.05 were considered statistically significant, with a power of 0.8. Results The study sample included 200 patients with a mean age of 46.6 ± 17.1, of whom 110 were women (55%). Ninety-three (46.5%) responded that they would be very interested in obtaining their physician's cell phone number, and an additional 83 (41.5%) would not object to obtaining it. Of the 171 patients (85.5%) who had e-mail addresses, 25 (14.6%) said they would be very interested in obtaining their physician's e-mail address, 85 (49.7%) said they would not object to getting it, and 61 (35.7%) were not interested. In practice only one patient had requested the physician's e-mail address and none actually had it. Conclusions Patients favored cell phones over e-mail for consulting with their treating physicians. With new technologies such as cell phones and e-mail in common use, it is important to determine how they can be best used and how they should be integrated into the flow of clinical practice.